2 - Crise financière et Ajustement par le Marché dans le Monde arabe: Quelles Perspectives? by Habib El Malki - Habib El Malki, (Africa Development, 1989)
The debt issue dominated the discourse of the 1980* s signalling international credit as the main form of accumulation in the world economy. It was founded on a new form of inter-dependence between debtors and creditors with the latter making sure that the former do not go bankrupt As a result, the debt issue overdeteimines everything subordinating concerns with growth and development The spiral of debt results from the transformation of the role of money and finance following the emergence of the electronic currency and a vast and unique global market erf capital managed by the computer and satellite links. Accelerated by the mobile mass of petro -dollars, this "Casino-economy" signals the growth of speculation at the expense of productive activity. Given the growing interventionist policy of financial institu- tions specially the IMF and the World Bank, for debtor countries, debt repayment has meant the intensification of inequalities, dependence, pauperization, loss of sovereignty and reversal of development priorities. Originating both from the global financial and monetary anarchy and internal financial policies, the debt of Arab countries is neither conjunctural nor transient Its specificities lie in the inter-regional flow of finance between Arab-countries. Although hetero- geneous in nature, agriculture and food dependency is a common profile of the debt structure in Arab countries. As elsewhere, Arab countries have turned to structural adjustment Programme as a solution. Conceived independently of the socioeconomic specificity of countries and igno- ring complexities in favour of simplification, SAP advocates universal recipes and market forces as a solution to all ills. Its depressive budgetary policy liberalization and restrictive social policy have meant giving priority to the export sector and downgrading the internal market. This aggravates social differentiation, marginalizing large sectors erf the population, impoveris- hing the middle class and threatening local based entrepreneurs. The past and recent history shows that an imposed market system is more a source of renewed domination than a source of liberation for countries . of the south-